Jogo pedagógico: facilitador do processo de ensino e de aprendizagem na alfabetização do 1º ano do ensino fundamental I - Higa, Salete Cristina Arfelli Martini (2012)
The ludic activity enables those who experience moments with himself mixing fantasy and reality moments enhancing perception and self-knowledge. In this case games are proposed in order to gather important information about how student thinks and learns. Therefore, the aim of this monograph is to understand the importance of developing educational games for students in the literacy process of the first year of elementary school. The methodology of this work was first literature as Vygotsky (1988), Kishimoto (2008), Emily Smith (2001), among others, and then as second choice was the methodology of study of case. The research subjects were students from the first year of elementary school. As a result it was observed the action of playing requires efforts on interpretations sort and develop information. The use of pedagogical game can be a great incentive for students, thus facilitating better understanding and assimilation of content in a relaxed and enjoyable way.